Predictors for early mortality in patients with implantable cardiac defibrillator for heart failure with reduced ejection fraction. (24th May 2021) - Cinier, G; Hayiroglu, MI; Pay, L; Yumurtas, AC; Tezen, O; Eren, S; Kolak, Z; Cetin, T; Ozcan, KS; Turkkan, C; Ozbilgin, N; Tekkesin, AI; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Implantable cardiac defibrillators (ICD) are recommended in heart failure with reduced ejection fraction (HFrEF) patients to reduce arrhythmic deaths. The only contraindication for not implanting ICD is life expectancy of less than 1 year. We aimed to identify risk factors associated with mortality within 1 year following the device implantation. Methods: Data from our hospital's electronic database system was extracted for patients who were implanted ICD secondary to HFrEF between 2009 and 2019. Those who died within 1 year following the device implantation were analyzed in the present paper. Multiple Cox regression analysis using the backward logistical regression method was applied to determine the best predictors that affect 1-year mortality Results: Overall 1107 patients were included in the present analysis. ICD was implanted in 77.2% and 22.8% for ischemic and non-ischemic HFrEF respectively. Mortality rate at 1-year following the device implantation was 4.7%. In multivariate analysis age [Hazard ratio (HR), 1.04; Confidence 95% Intervals (CI), 1.02 – 1.06; P = 0.001], atrial fibrillation (AF) (HR, 4.12; 95% CI, 2.34 – 7.24, P < 0.001), NYHA class > 2 symptoms (HR, 5.33; 95% CI, 2.92 – 9.73, P < 0.001), blood urea nitrogen (BUN) (HR, 1.02; 95% CI, 1.00 – 1.03, P = 0.03) and albumin (HR, 0.52; 95% CI, 0.34 – 0.80, P = 0.003) independently predicted 1-year mortality Conclusion: In patients with HFrEF and implanted ICD, older age, presence of AF and NYHA class > II symptoms, elevated BUN and reduced albumin levels predicted 1-year mortality.